Prognostic factors for the sequelae and severity of Guillain‐Barré syndrome in children. Issue 6 (23rd October 2019) - Estrade, Sophie; Guiomard, Clara; Fabry, Vincent; Baudou, Eloise; Cances, Claude; Chaix, Yves; Cintas, Pascal; Meyer, Pierre; Cheuret, Emmanuel
Abstract: Introduction: Guillain‐Barré syndrome (GBS) is an inflammatory polyradiculoneuritis. Our aim in this study was to describe the clinical characteristics and the long‐term sequelae of GBS in a French pediatric population. Methods: In this multicenter, retrospective study we evaluated clinical signs, radiological examinations, laboratory tests, treatments, and outcomes. Results: One hundred ten children were included in this investigation. These children presented with walking difficulties, muscle weakness, and cranial nerve impairment. Electrodiagnostic testing revealed 70% with acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and 16% with acute motor axonal neuropathy (AMAN). One hundred children received immunoglobulins. At follow‐up, 77% were cured, whereas 9% had sequelae, associated with an axonal form ( P < .01) and a short interval between symptom onset and hospitalization ( P < .01). The need for intubation was correlated with peripheral facial paralysis ( P < .01) and dysautonomia ( P < .01). Discussion: Although AIDP and AMAN present in a similar way, the axonal form is associated with a worse outcome.